Cartesian Product Of Interval Neutrosophic Automata (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We introduce Cartesian product of interval neutrosophic automata and prove that Cartesian product of cyclic interval neutrosophic automata is cyclic